A policy-practice gap? A comparative case study of the implementation gap in Irish and Italian asylum policy - Peroni, Claudia (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2025)
Over the last decade, the European Union experienced a sharp increase in the number of forced migrants, intensifying the challenge of receiving them in host countries. Asylum policy is highly contentious, increasingly securitised and involving multiple actors and governance levels. These complexities can produce gaps between asylum policy on paper and in practice. Yet, the many ways in which national and local context produce asylum policy remain understudied. This thesis analyses the factors influencing asylum policy implementation at the national, local and individual level. It compares asylum systems in Italy and Ireland, two countries which differ in political and economic context, numbers of forced migrants and asylum system design: the latter completely privatised in Ireland, public and heavily reliant on civil society in Italy. The thesis focuses on asylum street-level bureaucrats (SLBs), to examine whether different contextual elements cause differences in how they conceptualise their professional identity and carry out their work. The central research question of the thesis is: what shapes and characterises the implementation of Irish and Italian asylum policy at the national, local and individual level? This thesis addresses some gaps in existing research on EU asylum systems. First, it provides an organic qualitative analysis of the different levels, actors, contexts and dynamics involved in the implementation of asylum policy, paying particular attention to the socially constructed and relational elements which create connections between these levels, and to what these connections imply in terms of outcomes and experiences for forced migrants, local communities and workers. Such a holistic approach is still relatively lacking in research on asylum policy, but ultimately key to understanding its concrete implementation at the ground level. In fact, this thesis finds that the specificity of local contexts of implementation produces unique local ideas and practices of asylum; both research and policy should acknowledge the ultimately local scale of asylum and adopt a truly fine-tuned approach that embraces this complexity and diversity. Relatedly, this thesis addresses the lack of explicitly comparative research contrasting different models of asylum governance and asylum policy, and the consequences of these different designs on the functioning of the system. This approach enables insight into the different challenges and characteristics of different policy models, and on how the macro-level ultimately affects the daily micro-level. Finally, the thesis centres the experiences and subjectivities of an understudied group which is nonetheless fundamental in implementing asylum policy, namely frontline asylum workers in their capacity as street-level bureaucrats (SLBs). Existing research tends to focus on the perspectives of forced migrants themselves, policymakers or workers in specific contexts (usually emergency or detention centres); this thesis argues that studying 'ordinary' workers, who daily implement asylum policy and construct asylum on a local level, offers an insightful lens into how system design, local context and individual characteristics combine to produce unique local policy. The thesis examines different levels of production and implementation of asylum policy. National media and political narratives about forced migration are analysed to examine predominant interpretive frames, their use by different actors and their evolution over time. The framing of forced migration can impact the design and implementation of the asylum system, for example by influencing public discourses which in turn can shape local practices and attitudes toward forced migrants. In each country, predominant frames diverge across actors (politicians and newspapers) but tend to remain unchanged over time and in response to events perceived as pivotal. The construction, content and deployment of specific interpretive frames is a dynamic process: apparently divergent frames can reflect a similar discourse, or apparently similar frames can result from different country-specific processes. The design of the two asylum systems is probed through the lens of workers' experiences, to assess whether the privatised vs non-privatised model influences their satisfaction, professional identity, practices and challenges. Semi-structured interviews suggest that a non-profit system improves workers' experiences by providing value-based meaningfulness and interconnectedness with other public services. Conversely, a for-profit system provides less support in terms of available networks, regulation, transparency and accountability, and thus appears ill-suited to asylum policy, especially when located within a broader context of marketised state services. Finally, the thesis uses interviews with workers to examine the local construction of asylum policy at the local level within each country. In Italy, similarities and differences in policy implementation and outcomes are largely shaped by context-specific sociocultural and relational elements. Workers' off-duty mediation between migrants and community members fosters positive encounters that partially offset traditionally conservative political cultures and hostile attitudes; however, the same cultures cause workers to feel isolated and alienated from their community. Furthermore, SLBs' decision-making practices are always collegial and constrained by exhaustive rules, largely eliminating the need for individual discretion typical of SLBs and creating instead 'group discretionary' bureaucrats. In light of these findings, increased focus is needed on locality beyond a simple urban vs rural lens, and on asylum SLBs as 'doubly embedded' SLBs participating in both policy implementation and local context. Interviews with Irish asylum SLBs, on the other hand, show that the staff of private reception centres detach their work from the idea of belonging to an institutionalised asylum system, implicitly rejecting their role in perpetuating the system and their categorisation as street-level bureaucrats. Conversely, civil servants and volunteers active in the asylum system are able to critically reflect on the nature of the system, how it is influenced by its privatised character, and their own role within it. This disconnection between asylum SLBs and the policy regime they are an integral part of both influences and is caused by the marketised nature of the system, impeding the traditional role of street-level bureaucrats as bottom-up 'policymakers'.
APPROVED
Keywords: asylum policy; forced migration; policy implementation; street-level bureaucrats; Ireland; Italy; comparative case study